Variation and minimum number of samples for the character days after pollination in fiber palms germplasm (Research, Society and Development, 2023)
Was estimated the character days after pollination (DAP) in fiber palms from the Active Germplasm Bank - BAG of Embrapa Amazônia Oriental, in order to evaluate the number of days required from pollination to maturity, as well as to estimate the minimum number of evaluation. For this, 148 plants representing 32 accessions were evaluated. In each plant, a newly fertilized inflorescence was marked and followed until fruit maturation. The repeatability was estimated based on two, four and six inflorescences followed in 96, 45 and nine plants, respectively. The data obtained were submitted to basic statistical analyses and estimates of the repeatability coefficients (r) by means of four methods: analysis of variance (ANOVA); principal components based on the covariance matrix (CPCV) and correlations (CPC); and structural analysis based on the correlation matrix (AEC) and covariance matrix (AECV). The highest values were detected in the sample with four inflorescences by the principal components method based on the covariance matrix (PCVC) at the 80% level of reliability. Therefore, it is concluded that the fiber palms from this BAG have considerable variation for the character days after pollination (DAP), with two late and two early accessions for fruit maturation and indicating nine inflorescences as the minimum number of samples.